High‐spin square planar iron(II) alkali metal siloxide complexes – influence of the alkali metal and reactivity towards O2 and NO. Issue 8 (30th March 2021) - Beckmann, Fabian; Kass, Dustin; Keck, Matthias; Yelin, Stefan; Hoof, Santina; Cula, Beatrice; Herwig, Christian; Krause, Konstantin B.; Ar, Deniz; Limberg, Christian
Abstract: Complexes [L2 Fe][Li(DME)]2, 1(DME), {[L2 Fe][Na2 (DME)3 ]}∞, 2(DME) and [L2 Fe][K(DME)2 ]2, 3(DME) were synthesized by deprotonation of LH2 (LH2 =O(SiPh2 OH)2 ) with the respective alkali metal tert ‐butoxides followed by recrystallization from DME. It turned out that upon crossing over from Li + via Na + to K + counterions the structures of the high‐spin iron(II) complexes are increasingly distorted from a square planar towards a tetrahedral structure so that 3(DME) represents a borderline case, as indicated by the τ ‐values. The distortions are also reflected in the Mössbauer spectra through the quadrupole splittings. The compounds behave inert in contact with O atom transfer reagents but react rapidly with dioxygen. The reaction rates are too high to be determined even by stopped‐flow measurements quantitatively, but qualitatively it emerged that the rates increase from Li to Na to K. Using NO as an O2 surrogate an NO adduct with an S = 3/2 ground state was isolated where NO is coordinated in an end‐on binding mode, formally as a NO − ligand, with a significantly weakened NO bond. Abstract :